Graphene oxide induced enhancement of light-driven micromotor with biocompatible fuels. (March 2021) - Yang, Qianxian; Xu, Houyang; Wen, Hantao; Zhao, He; Liu, Xiaoya; Cai, Yuepeng; Wang, Hong; Dong, Renfeng
Highlights: A novel Cu2 O@GO micromotor has been successfully fabricated by simple one-pot method and can be efficiently propelled in a series of biocompatible fuels. Compared with conventional plain Cu2 O micromotors, the micromotors with GO (Cu2 O@GO) show more than 3 times faster speeds under the full range of visible light with biocompatible fuels. The Cu2 O@GO micromotors even can exhibit attractive near-infrared activated propulsion in a series of biocompatible fuels, such as glucose, leucine, and urea solutions. Abstract: A highly efficient light-driven cuprous oxide @ graphene oxide (Cu2 O@GO) micromotor which can be propelled with various biocompatible fuels is described. The Cu2 O@GO micromotors, which achieve enhanced photocatalytic performance by doping Cu2 O with GO, can be efficiently propelled by visible light and even near infrared light. Compared with conventional plain Cu2 O micromotors, which can only be driven by visible light, the Cu2 O@GO micromotors show more than 3 times faster speeds under the full range of visible light with biocompatible glucose fuel. In addition, due to the GO-induced enhanced photocatalytic performance and local photoinduced thermal effects, such motors can be powered by NIR with a series of biocompatible fuels, such as glucose, leucine, and urea solutions, with speeds reaching up to 11.39 µm s −1 (in glucose), which extends the excitation wavelength of photocatalytic micromotors to near-infrared light. This novel strategy of improving the performance of light-driven micromotors via GO doping has opened up a new and attractive path for the preparation of micromotors with potential applications in biological environments. Graphical abstract: Cu2 O@Graphene Oxide (Cu2 O@GO) micromotors exhibit excellent propulsions under harmless and low energy visible, even near infrared (NIR) light, in a series of biocompatible environment due to the attractive electrical properties and photothermal effects of GO. Image, graphical abstract